(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2023)
Streptomyces species are the dominant source of microorganisms involved in the production of broad-spectrum antibiotics used by many pharmaceutical and biotechnological sectors. A mangrove ecosystem with a saline and humid atmosphere harbours specific organisms that could produce significant bioactive agents that are applicable for many biomedical applications. The present study aimed to isolate, screen, with characterization and production of antimicrobial peptides from Streptomyces spp. from mangrove soil sediments. Mangrove soils were collected from four different sites on the Mangalore coast. The soil was pre-treated for the enrichment of actinomycetes and cultured with the use of five different media which exhibited distinctive morphological, biochemical, and phylogenetic features along with distinctive spore structure and arrangements by SEM image analysis. This led us to the identification of the two Streptomyces species, Streptomyces minutiscleroticus and Streptomyces albogriseolus. The antimicrobial screening was carried out to study their antagonistic property against the test pathogenic bacteria cultures of ATCC. In an attempt to explore peptide molecules with antimicrobial properties from actinomycetes cultures dwelling in the mangrove soil of Mangalore coast, we could enhance the peptide production in ISP2 medium for peptide production by S. minutiscleroticus and S. albogriseolus. Further, the minimum concentration of 0.01 mg microbial peptide was determined to inhibit the growth of pathogenic bacteria as assayed by broth dilution and plate assays. The LC-MS analysis revealed molecular weights of 25 kDa and 29 kDa antimicrobial peptides from S. albogriseolus and 31 kDa antimicrobial peptides were detected from S. minutiscleroticus.